Working in Steel : The Early Years in Canada, 1883-1935 - Heron, Craig (Book collections on Project MUSE., 2008)
Heron's examination of the impact of new technology in Canada's Second Industrial Revolution challenges the popular notion that mass-production workers lost all skill, power, and pride in the work process.